2020
DOI: 10.3390/ma13081926
|View full text |Cite
|
Sign up to set email alerts
|

Penta-C20: A Superhard Direct Band Gap Carbon Allotrope Composed of Carbon Pentagon

Abstract: A metastable sp3-bonded carbon allotrope, Penta-C20, consisting entirely of carbon pentagons linked through bridge-like bonds, was proposed and studied in this work for the first time. Its structure, stability, and electronic and mechanical properties were investigated based on first-principles calculations. Penta-C20 is thermodynamically and mechanically stable, with equilibrium total energy of 0.718 and 0.184 eV/atom lower than those of the synthesized T-carbon and supercubane, respectively. Penta-C20 can al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…First-principles calculations based on density functional theory (DFT) are among the most reliable and popular microscopic theories in material science. This method has a high ability to predict the material structures and properties [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Yang et al [ 21 ] predicted a novel high-pressure superhard BN phase at high pressure through a developed particle swarm optimization (PSO) algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…First-principles calculations based on density functional theory (DFT) are among the most reliable and popular microscopic theories in material science. This method has a high ability to predict the material structures and properties [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Yang et al [ 21 ] predicted a novel high-pressure superhard BN phase at high pressure through a developed particle swarm optimization (PSO) algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the similarity-based match is performed for a set of crystalline allotropes from the literature (Figure S7). The pbz/cF288 training allotrope consisting of acetylenes and 6-rings matches the three graphdiyne ( GDY-1 , GDY-2 , and GDY-3 ) crystal structures reported by Matsuoka et al 13 4 6 T10 of the training set and oC14 predicted by Yang et al are determined to be similar, both being tubulanes containing 4-, 6-, and 8-tubes.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The tP20 in the form of an octahedral tube array, predicted by Fan et al, is found to be structurally similar to 3 3 .4 3 T28 . For other external allotropes, such as tP16 , penta-C20 , o-C240 , oC240 , and oC48 , their best-matched counterparts in the training set are also given in Figure S7.…”
Section: Results and Discussionmentioning
confidence: 99%
“…More and more materials composed of light elements have been found by researchers . Among them, carbon allotrope [1][2][3][4][5][6][7][8][9][10] and boron nitride polymorph [11][12][13][14][15][16] are representatives, and BN polycrystalline materials can be used not only as superhard materials but also as two-dimensional magnets [17]. Recently, a metastable carbon allotrope with sp 3 -hybridized, denoted as Penta-C 20 , was proposed and studied by Zhang et al [1].…”
Section: Introductionmentioning
confidence: 99%